Spirited Politics: Religion and Public Life in Contemporary Southeast Asia - George, Kenneth M.; Willford, Andrew C. (Cornell University Press, 2004)
The essays in Spirited Politics throw light on predicaments that spring from the intersection of religion, ethnicity, and nationalism in contemporary Southeast Asian public life. Covering material from Indonesia, Malaysia, Thailand, and the Philippines, the contributors explore the calamities and ironies of Southeast Asian identity politics, examining the ways in which religion and politics are made to serve each other.